Jean de La Gessée’s Henrias: Literary Features and Sources of Imitation - Šileikienė, Rasa Marija (Senoji Lietuvos literatūra, 2025)
The second part of a two-article series continues with the analysis of Henrias, a collection of Latin occasional poems written by a poet of the Valois court who wrote under the pseudonym of Jean de La Gessée, during the election of Henry Valois in 1573. The collection is analysed in terms of literary form, theme, and ideas. The article describes the main motifs and images used to convey the political narrative and propaganda message and to create an ‘epic’ image of Henry Valois, the future ruler of the Polish-Lithuanian Commonwealth, and reveals the sources of literary influence and imitation. The connections between this collection and La Gessée’s other works are indicated, including those that were likely written by the same author under other pseudonyms. One such work is the epic poem Élection du sérénissime duc d’Anjou, roy de Poulongne [...] published by Paul de Vollant in 1573. The similarities between the text of this poem and Henrias, the circumstances of its publication, and other aspects would allow this poem to be attributed to La Gessée (i.e., the court poet Louis d’Amboise, who used both these pseudonyms; we have examined this identification of the author in previous articles, and it remains the subject of further and more detailed research).La Gessée’s panegyric ‘epic’ works La Rochelleide and Henrias, published in French and Latin in 1573, belong to the wave of epic-style works that arose in French literature in the 1570s inspired by Ronsard’s Franciade and are also inspired by important events of the time (religious wars, the election of Henry Valois). This is the poetry of ‘current events’ and ‘news’, about recent developments and Henry Valois, the ‘hero of the present’. In the context of neo-Latin Renaissance literature, Henrias continues the tradition of epic panegyrics dedicated to rulers and nobles. The choice of the genre, poetic forms, and their composition was influenced by the neo-Latin panegyrics, epic poems, and epithalamia of various countries from the late fifteenth century to the first decades of the sixteenth century (among which connections with Giovanni Michele Nagonio’s panegyric poems can be discerned) and the trends of common-European neo-Latin poetry of the mid-sixteenth century.The main part of Henrias consists of an epic panegyric, which has the traditional rhetorical structure of an encomium: a solemn introduction, a description of the family of Henry, Duke of Anjou, and its deeds, a characterisation of his person, his achievements, and a discussion of his ‘virtues’ (the latter is presented as ‘advice to the young ruler’). In terms of the genre, structure, style, and lexicon, it followed the panegyrics of Claudian, a Late Antiquity poet. Based on existing studies of Claudian’s reception in Renaissance literature and on our analysis of the text, it can be argued that Panegyric is a particularly striking (perhaps one of the most striking) example of Claudian’s reception and imitation in sixteenth-century epic and panegyric poetry.Rich in Claudian’s quotations, the text of the panegyric reveals the implied projection of its dedicatee and subject, Henry Valois, onto the figure of Stilicho, the hero of Claudian’s panegyrics, a general and politician who attained power through his ‘virtue’ (virtute) (an analogy: Henry Valois is elected from among his peers because of his ‘virtue’). Stilicho’s Vandal origins are also significant for this projection. According to a medieval theory of the origin of the Polish nation, the Vandals are considered to be the ancestors of the Poles. Despite the fact that historians had been sceptical of this theory since the mid-sixteenth century, it continued to live on in the literary tradition. In literary works, Stilicho was often included in the lists of rulers of Poland and Lithuania, i.e., he was a locus communis of (pseudo)historical narratives in the cultural space of the Polish-Lithuanian Commonwealth. Thus, in this panegyric Henry Valois can be regarded as the ruler of Stilicho’s homeland. The article also examines how traditional topoi borrowed from Renaissance literature were used in Henrias to convey the political ideology of the 1573 election and the French court (the images of the embassy to Achilles on Skyros, the images of the ‘golden age’, and the reign of Astraea, the goddess of justice, the vision of Pax Valesiana created on the model of ancient Rome, which also encompasses the Polish-Lithuanian Commonwealth ruled by Henry Valois ‘to the distant sea’, the myth of French origin from the Trojans, and so on).Textual analysis of Henrias shows that the author imitates the works of such authors of Classical and Late Antiquity as Virgil, Ovid, Horace, Cicero, Claudian, Lactantius, to a lesser extent Juvenal, Catullus, Tibullus, Lucretius, Lucan, Seneca, Silius Italicus, Statius, Sidonius Apollinaris, and several others, or draws on them in other respects. In quantitative terms, the majority of borrowings came from Claudian’s works, fewer from Virgil, Ovid, and Horace, and even fewer from other authors. Henrias shows traces of influence and/or vocabulary from Renaissance authors Ugolino Verino, Jacopo Sannazaro, Marco Girolamo Vida, and Marcellus Palingenius Stellatus. Stylistically close to the poet were also various neo-Latin authors from different countries, such as Matteo Andronico, Iacobus Bonus Racusaeus, and Paulus Crosnensis (their influence is evident both in Henrias and in La Gessée’s other works in Latin). He was clearly influenced by the works of the Latin poets of the Pléiade (similarities with Étienne Jodelle’s occasional poetry). Without a doubt, La Gessée was familiar with and had access to the works of Polish and foreign chroniclers and cosmographers who wrote about Poland and Lithuania, and he was also interested in the works of poets from these lands. Text analysis shows that he read and used the poem Bellum Prutenum (1516; The Prussian War) by Joannes Vislicensis and probably Georg Sabin’s Poemata (1558), a poetry collection in Latin. The article compares the description of the Polish-Lithuanian Commonwealth in Henrias (which was one of the first descriptions of Poland-Lithuania in French literature) with the text of Joannes Vislicensis’s poem.
Keywords: Polish-Lithuanian Commonwealth in the sixteenth century; Henry Valois; Neo-Latin literature in the sixteenth century; Henrias; Jean de La Gessée; Louis d’Amboise